Regional differences and coronary microvascular dysfunction in heart failure with preserved ejection fraction - Erhardsson Mikael; Faxen Ulrika Ljung; Venkateshvaran Ashwin; Svedlund Sara; Saraste Antti; Fermer Maria Lagerström; Gan Li-Ming; Shah Sanjiv J.; Tromp Jasper; Lam Carolyn S. P.; Lund Lars H.; Hage Camilla (Wiley, 2025)
Aims
In heart failure with preserved ejection fraction (HFpEF), regional heterogeneity of clinical phenotypes is increasingly recognized, with coronary microvascular dysfunction (CMD) potentially being a common shared feature. We sought to determine the regional differences in clinical characteristics and prevalence of CMD in HFpEF.
Methods and results
We analysed clinical characteristics and CMD in 202 patients with stable HFpEF (left ventricular ejection fraction ≥40%) in Finland, Singapore, Sweden, and United States in the multicentre PROMIS-HFpEF study. Patients with unrevascularized macrovascular coronary artery disease were excluded. CMD was assessed using Doppler echocardiography and defined as coronary flow reserve (adenosine-induced vs. resting flow) < 2.5. Patients from Singapore had the lowest body mass index yet highest prevalence of hypertension, dyslipidaemia, and diabetes; patients from Finland and Sweden were oldest, with the most atrial fibrillation, chronic kidney disease, and high smoking rates; and those from United States were youngest and most obese. The prevalence of CMD was 88% in Finland, 80% in Singapore, 77% in Sweden, and 59% in the United States; however, non-significant after adjustment for age, sex, N-terminal pro-brain natriuretic peptide, smoking, left atrial reservoir strain, and atrial fibrillation. Associations between CMD and clinical characteristics did not differ based on region (interaction analysis).
Conclusions
Despite regional differences in clinical characteristics, CMD was present in the majority of patients with HFpEF across different regions of the world with the lowest prevalence in the United States. This difference was explained by differences in patient characteristics. CMD could be a common therapeutic target across regions.